Neurodevelopmental Outcome and Adaptive Behavior in Preterm Multiples and Singletons at 1 and 2 Years of Corrected Age - Squarza, Chiara; Gardon, Laura; Giannì, Maria Lorella; Frigerio, Andrea; Gangi, Silvana; Porro, Matteo; Mosca, Fabio; Picciolini, Odoardo (Frontiers in Psychology, 2020)
Background Recent literature has investigated the role of multiple birth on neurodevelopmental outcomes of premature infants, especially extremely preterm ones. Multiple gestations are often associated to increased neurodevelopmental disability. Actually, research findings are controversial. Objective To compare the neurodevelopmental and behavioral outcomes of multiples and singletons in a cohort of preterm infants ≤28 weeks gestational age at 1 and 2 years of corrected age. Methods The study included 86 infants, born from January 2014 to September 2017 and enrolled in the follow-up program provided at authors’ Institution. Exclusion criteria included: major brain lesions and malformations, severe neuro-sensorial deficits, genetic syndromes, single-twin survivors. Thirty four multiples were compared to 52 singletons, using the Griffiths Mental Development Scales and the Child Behavior Checklist 1½–5. Statistical analysis was based on ANOVA techniques to test group differences. A p < 0.05 was considered statistically significant. Results The neurodevelopmental outcomes of multiples and singletons at 1 and 2 years of corrected age did not significantly differ at a general level (p > 0.05). Multiples showed significantly lower mean scores than singletons at 1 year in Locomotor (87.15 ± 11.94 vs. 92.48 ± 11.59) and Personal-Social (84.88 ± 10.25 vs. 89.63 ± 8.19) subscales. Considering the behavioral outcomes, higher rates of externalizing problems were observed in multiples at 2 years (54.27 ± 9.64 vs. 49.31 ± 10.39). Conclusion The slightly lower neurodevelopmental outcome showed by multiples, especially in the gross-motor and personal-social domains at 1 year, might be related to the specific environmental condition they experience. Multiple birth may affect mother’s sensitivity to infant’s needs and infant’s acquisition of emotional and behavioral regulation. This affects the separation process and the acquisition of the independent walking and other gross-motor skills. Being multiples might also induce an hyperstimulation and this could explain their higher vulnerability to externalizing problems (impulsiveness, hyperactivity, attention deficits). Additionally, males are more affected by the multiple condition than females.